The Effectiveness of Learn English Vocabulary Application in Enriching Students’ Vocabulary Learning - Fitriah, Putri; Eusabinus Bunau; Eka Fajar Rahmani; Rahayu Apriliaswati; Eni Rosnija (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This research was conducted using pre-experimental research to determine the effectiveness of Learn English Vocabulary application in enriching students’ vocabulary learning among the 7th-grade students of SMP Negeri 20 Pontianak. The total population was 186 students, and the sample was 15 students from class F. The data were gathered using a test in a form of multiple choices with a total of 25 questions. The test was distributed in a form of a pre-test and a post-test. The data were analysed using Microsoft Excel and SPSS v.26 with a 5% significance level. It showed that there was an enrichment of students’ vocabulary learning. It was indicated by the values of Sig. (2-tailed) score from the t-test calculation which was 0.000. It means the value was lower than 0.05. The hypothesis testing result also strongly provides evidence by the acceptance of the hypothesis alternative with a t score of 8.5 higher than the ttable score of 2.145. Moreover, the effect size calculation showed that the significant effect of the application is in a score of 2.1 which is interpreted as a strong effect. Therefore, the use of Learn English Vocabulary application is significantly effective in enriching students’ vocabulary learning.